Feature Analysis of Ship Emission Under China’s ECA Policy: A Perspective from Shanghai - Zhu, Yibing; Ge, Jiawei; Wang, Xuefeng; Xu, Zhipeng (International Journal of Management and Sustainability, 2018)
The prosperity of maritime commerce brings economic benefits to port cities; however, the air pollution along with the calling of ships undermines the local environment. Being conscious of this, the Chinese government officially issued its agenda on emission control areas (ECA) along her coastal areas at the end of 2015. This paper measures the features of ship emission via an activity-based approach based on AIS data. The air pollutant emission from 24 filtered ocean-going vessels calling the port of Shanghai are calculated, where the emission reduction rates are identified and classified through ship type, engine model and sailing conditions. Findings show that the ECA scheme has an effective impact on reducing the ship emission. The average emission reduction rates of oil tankers/chemical ships, container ships, bulk carriers, liquefied gas ships, general cargo ships, cruise ships and roll-on-roll-off ships are 30.52%, 23.28%, 20.65%, 14.23%, 13.84%, 12.66% and 12.30% respectively. Implications for the next phase of ECA Act are proposed in enacting stricter emission control standards and expanding the scope of ECA after 2020.